In Vitro Experimental Assessment of Ethanolic Extract of Moringa oleifera Leaves as an α-Amylase and α-Lipase Inhibitor - Adebanke Ogundipe; Babatunde Adetuyi; Franklyn Iheagwam; Keleko Adefoyeke; Joseph Olugbuyiro; Oluseyi Ogunlana; Olubanke Ogunlana (Biochemistry Research International)
Background and Objectives. Moringa oleifera has been scientifically reported to have effects on diabetes and obesity. An explanatory mechanism on how the plant exerts its enzyme inhibitory activities are yet to be detailed. This study was aimed at carrying out an in vitro assessment of ethanolic extracts (AEEs) of M. oleifera leaves for their antioxidant, antidiabetic, and antiobesity activities. Methods. Phytochemical screening, antioxidant activity, α-amylase, and α-lipase inhibitory assessment were carried out on Moringa oleifera extract. Results. The result of the phytochemical screening revealed the presence of total phenolic, flavonoid, tannin, and alkaloid contents of values 0.070 ± 0.005 mg gallic acid equivalent/g, 0.180 ± 0.020 mg rutin equivalent/g, 0.042 ± 0.001 mg tannic equivalent/g, and 12.17 ± 0.001%, respectively, while the total protein analysis was 0.475 ± 0.001 mg bovine serum albumin equivalent/g. Ferric reducing antioxidant power (FRAP) and total antioxidant capacity (TAC) values were 0.534 ± 0.001 mg gallic acid equivalent/g and 0.022 ± 0.00008 mg rutin equivalent/g, respectively. Diphenyl-2-picrylhydrazyl (DPPH), ABTS (2,2′-azino-bis (ethylbenzothiazoline-6-sulfonic acid)), and nitric oxide (NO) assays showed the extract to have a strong free radical scavenging activity. The 50% inhibitory concentration (IC50) values of the lipase and amylase activities of the extract are 1.0877 mg/mL and 0.1802 mg/mL, respectively. Conclusion. However, α-lipase and α-amylase inhibiting activity of M. oleifera could be related to the phytochemicals in the extract. This research validates the ethnobotanical use of M. oleifera leaves as an effective plant-based therapeutic agent for diabetes and obesity.